Kompleksowe usługi logistyczne : przegląd podstawowych koncepcji - Kuriata, Andrzej; Gojlik, Anna (Complex Logistics Services : Barsic Concepts Reviev, 2005)
The role and significance of complex logistics services is dynamicly increasing in the open and dispersed business environment that is characteristic of logistics networks. An analysis of subject scope of complex logistics service, presented in the paper, indicates its permanent evolution from the basic transport activities, where services significantly exceeding transport, forwarding and even traditional logistics are joined to. It finds its expression in developed services portfolio offered by 4PL that co-ordinates the flow of goods and information in wide network structures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 241-247